PENGABDIAN MASYARAKAT DALAM MENDUKUNG PELAYANAN KESEHATAN MELALUI DONOR DARAH SUKARELA DAN PEMERIKSAAN KESEHATAN DASAR DI UIN SALATIGA: APLIKASI TEKNOLOGI ELEKTROMEDIS DALAM PENYULUHAN KESEHATAN - Kuspranoto, Abdul Haris; Puspita, Rina; Nadzifuz Zaki, Syauqi; Ulin Nuha ABA, Muhammad; Ahmad Ilham, Gus (LPPM POLBITRADA, 2025)
Health is a basic right that greatly affects the quality of life of the community, but there are still many individuals who are unaware of the importance of regular health checkups and voluntary blood donation. Based on this background, this community service activity aims to raise awareness among the community, especially students at the State Islamic University (UIN) Salatiga, about the importance of basic health checkups and contributing to blood donation activities. The problems faced are low public participation in voluntary blood donation and a lack of understanding about early detection of metabolic diseases. The objectives of this activity are to provide free health checkups, organize voluntary blood donations, and provide education about healthy lifestyles and the importance of regular blood donation. The methods used in this activity were educational, preventive, and collaborative approaches, involving electromedical technology for blood sugar, uric acid, and cholesterol checks using portable devices that enable fast and accurate results. The results of this activity showed high participant participation in blood donation and health check-ups, as well as enthusiasm among participants for the health education provided. This activity successfully raised public awareness about the importance of health check-ups and blood donation, and introduced the use of effective electromedical technology in facilitating efficient health check-ups.